Abdominal subcutaneous adipose tissue insulin resistance and lipolysis in patients with non‐alcoholic steatohepatitis. Issue 7 (11th March 2014) - Armstrong, M. J.; Hazlehurst, J. M.; Hull, D.; Guo, K.; Borrows, S.; Yu, J.; Gough, S. C.; Newsome, P. N.; Tomlinson, J. W.
<x xml:space="preserve">Abstract</x> Background Systemic insulin resistance (IR) is a primary feature in non‐alcoholic steatohepatitis (NASH), however, there remain limited data on tissue‐specific insulin sensitivity in vivo. Methods We examined tissue‐specific (adipose, muscle and liver) insulin sensitivity and inflammation in 16 European Caucasian patients with biopsy‐confirmed NASH and in 15 healthy controls. All underwent a two‐step hyperinsulinaemic euglycaemic clamp incorporating stable isotope measurements of carbohydrate and lipid metabolism with concomitant subcutaneous adipose tissue (SAT) microdialysis. Results Hepatic and muscle insulin sensitivity were decreased in patients with NASH compared with controls, as demonstrated by reduced suppression of hepatic glucose production and glucose disposal (Gd) rates following insulin infusion. In addition, rates of lipolysis were higher in NASH patients with impaired insulin‐mediated suppression of free fatty acid levels. At a tissue specific level, abdominal SAT in patients with NASH was severely insulin resistant, requiring >sixfold more insulin to cause ½‐maximal suppression of glycerol release when compared with healthy controls. Furthermore, patients with NASH had significantly higher circulating levels of pro‐inflammatory adipocytokines than controls. Conclusion NASH patients have profound IR in the liver, muscle and in particular adipose tissues. This study represents the first in vivo description of dysfunctional SAT in patients with NASH.